Study of stagger-tuning in the gyroklystrons - Chauhan M.S.; Jain P.K. (My University, 2025)
In present paper, the detailed study of stagger tuning has been carried out for multicavity gyroklystrons.The present analysis is based on the point-gap model for gyroklystrons in which the size of the cavities assumed much smaller than the drift sections.Therefore, we can assume that the effect of electron ballistic phase bunching took place only in the long drift sections whereas the electron energy modulation taking place in the short cavities.These assumptions help us to obtain the necessary equations for studying the effect of stagger tuning in gyroklystrons.The results obtained here for two and three cavity gyroklystrons clearly demonstrate the bandwidth enhancement, decrease in gain and overall increase in gain-bandwidth product due to stagger tuning.